2020
DOI: 10.1186/s13071-020-04241-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antigenicity of the Babesia caballi spherical body protein 4 (SBP4)

Abstract: Background: The tick-borne intra-erythrocytic apicomplexan Babesia caballi is one of the etiological agents of equine babesiosis, an economically important disease of equids in most tropical and subtropical areas of the world. Discovering candidate antigens for improved diagnostic tools and vaccines remains needed for controlling equine babesiosis. This study describes the B. caballi sbp4 (Bcsbp4) gene and protein (BcSBP4) and analyzes its antigenicity in infected equids. Methods: BLAST searches of an uncurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Spherical body proteins (SBPs) are specific proteins to Babesia spp. and Theileria spp., which are localized in the cytoplasm of erythrocytes and get involved in the secretion of apical organelles during the merozoite stage and lead to a unique mechanism of invasion ( 62 , 63 ). Multiple sequence alignments were performed between B. gibsoni genome and SBPs (SBP2, SBP3, and SBP4) from B. bovis.…”
Section: Resultsmentioning
confidence: 99%
“…Spherical body proteins (SBPs) are specific proteins to Babesia spp. and Theileria spp., which are localized in the cytoplasm of erythrocytes and get involved in the secretion of apical organelles during the merozoite stage and lead to a unique mechanism of invasion ( 62 , 63 ). Multiple sequence alignments were performed between B. gibsoni genome and SBPs (SBP2, SBP3, and SBP4) from B. bovis.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in many rural areas of Egypt, horses, donkeys, mules, and ponies are often used as working equids. These animals assist personnel in a variety of sectors, including agriculture and construction, help farmers in soil drilling and public transportation, and contribute to sustaining the livelihoods of millions of people [5,6].…”
Section: Equinesmentioning
confidence: 99%
“…This disease is caused by blood-borne piroplasmids, mainly Babesia and Theileria. It occurs frequently in rural areas of developing countries, including Egypt, where there is still a huge reliance on working equines, which include horses, donkeys, mules, and ponies [5][6][7]. Particularly, camels are an economically significant multipurpose animal that has been utilized traditionally as an important source of milk, meat, and wool, and they are widely distributed in Africa, the Middle East, and Northern India [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas of many developing countries, including Egypt, there is a huge reliance on working equids, which include horses, donkeys, mules, and ponies. These animals play important roles in sustaining the livelihoods of millions of people by providing support in industries that include agriculture, construction, tourism, mining, and public transport [1,2]. The health and welfare of domesticated equids are often overlooked in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations on vector competence for T. haneyi has not been reported [8]. Infection with T. equi and B. caballi can cause severe economic losses in the equine industry due to the cost of treatment, especially for acutely infected horses, which, in the absence of appropriate treatment, can die [2]. It was found that T. haneyi rarely causes clinical signs in field horses [9], even in splenectomized horses experimentally infected with T. haneyi using the intravenous (IV) route [5,10].…”
Section: Introductionmentioning
confidence: 99%